2020
DOI: 10.1186/s13578-020-00402-6
|View full text |Cite
|
Sign up to set email alerts
|

Sirt6 opposes glycochenodeoxycholate-induced apoptosis of biliary epithelial cells through the AMPK/PGC-1α pathway

Abstract: Background: Induction of biliary epithelial cell apoptosis by toxic bile acids is involved in the development of cholestatic disease, but the underlying molecular mechanism is not clear. The purpose of this study was to investigate the molecular mechanisms involved in Sirt6 protection against the apoptosis of human intrahepatic biliary epithelial cells (HiBEC) induced by the bile acid glycochenodeoxycholate (GCDC). Results: Sirt6 was either overexpressed or knocked down in HiBEC, with or without GCDC pretreatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…65 Moreover, recent studies showed that SIRT6-mediated AMPK activation reduced mitochondrial dysfunction in either high-glucose-cultured podocytes or glycochenodeoxycholate-pretreated biliary epithelial cells. 66,67 Our results showed that SIRT6 and AMPK-PGC-1α-AKT signaling were further inhibited by diabetic MI/R injury. Long-term melatonin administration reduced the vulnerability of diabetic heart toward MI/R injury by preserving mitochondrial quality control and activating SIRT6 and AMPK-PGC-1α-AKT signaling.…”
Section: F I G U R E 1mentioning
confidence: 71%
“…65 Moreover, recent studies showed that SIRT6-mediated AMPK activation reduced mitochondrial dysfunction in either high-glucose-cultured podocytes or glycochenodeoxycholate-pretreated biliary epithelial cells. 66,67 Our results showed that SIRT6 and AMPK-PGC-1α-AKT signaling were further inhibited by diabetic MI/R injury. Long-term melatonin administration reduced the vulnerability of diabetic heart toward MI/R injury by preserving mitochondrial quality control and activating SIRT6 and AMPK-PGC-1α-AKT signaling.…”
Section: F I G U R E 1mentioning
confidence: 71%
“…PGC‐1α is upstream of NRF1/NRF2, and TFAM regulates mtDNA replication and cellular oxidative metabolism (J. Li, Yu et al, 2020). Our results found that APAP treatment increased ROS production and decreased PGC‐1α levels.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, Wang et al [14] revealed that upregulation of cardiac SIRT6 exerted a positive effect on myocardial AMPK signaling and eventually protected against myocardial ischemia/reperfusion (MI/R) injury. Recent evidence also suggests that the SIRT6-AMPK pathway inhibits mitochondrial abnormalities in podocytes or biliary epithelial cells [15,16] . In view of these critical findings, we hypothesized that in diabetic conditions, SIRT6 upregulation might retards diabetes-induced ventricular remodeling through the AMPK pathway.…”
Section: Introductionmentioning
confidence: 94%
“…Recent evidence also suggests that the SIRT6-AMPK pathway inhibits mitochondrial abnormalities in podocytes or biliary epithelial cells. [15,16] In view of these critical findings, we hypothesized that in diabetic conditions, SIRT6 upregulation might retards diabetes-induced ventricular remodeling through the AMPK pathway.…”
Section: What Are the Clinical Implications?mentioning
confidence: 99%